The Phenomenon of Marriage Contract Repetition After Nikah Siri To Prevent Fitnah - Putri Jasmine Al Zhahra; Yusdi Haq (Fakultas Syariah INSURI Ponorogo, 2026)
Marriage in Islam is regarded as a sacred covenant (mitsaqan ghaliza) aimed at preserving religion, honor, and lineage. In the context of increasingly intensive interaction during the premarital preparation period, some Muslim couples choose to conduct a religious marriage contract (nikah siri) before official state registration to avoid potential social suspicion and moral concerns. This study aims to analyze the practice of repeating marriage contracts after nikah siri and to examine its relevance from the perspective of maqashid al-sharia. This research employs a qualitative method with a case study approach involving three Muslim participants who conducted a religious marriage contract before official state registration. Data were collected through in-depth interviews and analyzed using descriptive-analytical techniques. The findings indicate that the initial religious marriage contract is perceived as a precaution (ihtiyath) to preserve honor and prevent actions that approach immorality during the wedding preparation period. The repetition of the marriage contract is not intended to validate the first contract but rather to obtain legal recognition and administrative protection. From the perspective of maqashid al-sharia, this practice aligns with the objectives of preserving religion, honor, and lineage.